Integration of Local Wisdom and Collaborative Governance in Tegal Harum Village, Denpasar City - Ni Made Rosita Dewi; I Gusti Ngurah Desta Permana Putra; Ni Kadek Tasya Pranawa Dewi; I Gede Eka Pramana Putra; Ni Putu Dinda Kalpika Putri (International Journal of Science and Society, 2026)
The Transformation of village governance after the enactment of Undang-Undang Nomor 3 Tahun 2024 in respect of Villages has opened up space for strengthening village autonomy and encouraging the implementation of Good Governance principles at the local level. In this context, the Collaborative Governance approach is a relevant conceptual framework for examining multi-actor involvement in the public decision-making process in a participatory, responsive, and inclusive manner. This study seeks to analyze how Collaborative Governance practices are carried out in the governance of Tegal Harum Village, as well as how the manner in which local Tri Hita Karana values are incorporated into the collaborative process among the village government, traditional villages, communities, and the private sectors. This study employs a qualitative descriptive approach, with data collected through observation, in-depth interviews, literature review, and document analysis. The informant determination technique used is purposive sampling consisting of representatives of the village government, traditional villages, communities, and the private sector. This research is expected to show the collaboration carried out in the governance of Tegal Harum Village, as well as the integration of local Tri Hita Karana values in the collaborative process between the village government, traditional village, community, and private sector.